Dinámica del aprovechamiento de los recursos naturales de la cuenca media - alta del río nanay, loreto, Perú base para los lineamientos de un desarrollo rural sostenible - Cabudivo Moena, Abrahan (2008)
The present research has been done in the middle and high basin of Nanay river with the purpose to propose lines of integral development of the natural resources from the communities, beganning by the characteristics of the dynamic and its exploitation. The methodology includes a set of the organized community (the whole community) and the profitable resources withc arrive at the market through a direct contac with the extractor. The exploitation has been mainly characterized with six natural resouces: leaves of Lepidocaryum tessmanii; “Irapay”; Mauritia flexuosa, “aguaje”, fruit, Jessenia polycarpa “Ungurahui” fruit, fishing, hunting and the wood extraction for building, the sawdust and the firewood. It has been reduced the “Irapay” leaves exploitation from 2002 to 2007, until 7`200,000 units (17%), aguaje fruit until 8,708 kg (72%) and the ungurahui fruit until 805 Kg (77%), deer meat until 4800 kg (28%) and wood for building until 9400 units (44%). However, the fishing activity (7500 kg) the wood for the sawdust (838 pieces) and the firewood (2 161 m3) which have increased in 6%, 119% and 1,171 % respectly. There are 31 illegal extractors in fishing, 17 in wood for the sawdust and 16 in wood for building. The rate of disafforestation is 728 ha/year. After to determine the soio-economical and enviromental characteristics of the area which let us to identify with more details the development and the usage of the natural resources by the human populations. It has been elaborated a proposal about an integral development of the natural resorces which must adopt and apply in other basins with a high importance, with the authorieties` support, as a way to reduce, control and revert the accelarated processes of the environmental damage, the natural resouces and the lost of the biological diversity. For those reasons, this proposal should be the main component of the national enviromental politics, of conservation and the sustainable usage of the natural resources.